Enhanced Electromagnetic Interference Shielding Effectiveness of Lightweight Polymethyl Methacrylate /Graphene/Silver Hybrid to Reduced Pollution and Healthcare - Ali, Nadia A.; Badiaa I. Alawi (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
The growth of using electronic devices has led to the development of a new pollution type that has been referred to as noise, radio frequency interference, or electromagnetic radiation (EM). The identification of lightweight PMMA/Gr/Ag nanocomposites has led to the discovery of a new hybrid polymer composite. Electrical conductivity, High Electromagnetic (EM) Shielding Effectiveness (SE) in a frequency range of 8.20-12.40GHz (x-band), dielectric characteristics, and differential thermal analysis were used to examine PMMA/Gr/Ag. Using the solvent casting process, a hybrid PMMA/Gr/Ag nanocomposite was created. The hybrid composite’s electrical conductivity demonstrates that D.C conductivity is around 1.6×10-6 S/ cm as concentration is attained at 0.5% for Ag and 0.5% for Graphene, and that σac (ω) is frequency increases with increases in frequency. All PMMA/Gr/Ag nanocomposites exhibit decreasing dielectric properties (ɛ´, ɛ´´, tan δ) with increasing frequency. It was discovered that SE is highly dependent on Graphene and Ag, with the maximum SE attenuation recorded at 0.5wt% of Graphene and Ag being 11 dB at 12 GHz. Test of DTA shows that exothermic reactions with the dominating weight take place at (200–300)°C. PMMA matrix of PMMA/Gr/Ag nanocomposites displayed unique dispersion of the silver & graphene particles, according to FESEM results.